Evaluation of a Porcine deltacoronavirus eradication program in a full-cycle pig farm in Peru - Huaman, Jhonas Vicente; Quispe, Oscar E Gómez (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: In this case report, we report for first the time the presence of porcine deltacoronavirus (PDCoV) in Peru (October 2019) and Latin America, and we present a control and eradication program using feedback (exposure)/controlled homogenization in a pig farm. Materials and Methods: This farm is located in the eastern jungle of Peru. Initially, clinical signs that appeared to be infectious diarrhea were detected, but the disease rapidly progressed to green diarrhea, vomiting, and increased mortality in piglets. These symptoms were compatible with those produced by porcine epidemic diarrhea virus and transmissible gastroenteritis virus, but also with PDCoV. Because the disease could not be diagnosed by clinical signs and symptoms, analysis by real-time polymerase chain reaction was used. Implementation of a feedback/controlled homogenization program was quickly planned, accompanied by the closure of the farm, animal and farm health strategies, and its respective monitoring. Results: At the farm level, between 1 and 9 weeks after application of the program, the samples were positive for PDCoV, but at week 10, they were negative. At week 12, the weaned and fattening piglets gradually became populated as negative animals. In the follow-up before the opening of the farm, all the piglets were negative. In the final verification, gilts (week 35) entered the breeding area as replacements only after being tested negative for PDCoV. Conclusion: A rigorous feedback/controlled homogenization program and complementary measures led to eradicating PDCoV from the farm. J. Adv. Vet. Anim. Res., 8(2): 300-306, June 2021